A PESTEL ‐ SWOT Matrix Analysis of Sustainable Aquafeed Sector: A Case of Kenya's Fish Feed Sector - Esther Magondu; Lucy Njogu; Kevin Ouko; Jimmy B. Mboya; Mavindu Muthoka; Rodrigue Yossa; Jonathan Munguti; Mary A. Opiyo; Menaga Meenakshisundaram; Chrysantus M. Tanga; Kevin Obiero (Reviews in Aquaculture, 2025)
Global demand for seafood continues to rise, positioning aquaculture as a critical pathway for improving food security, nutrition, and rural livelihoods. In Kenya, the aquaculture sector remains constrained by structural challenges, with fish feed accounting for 60%–70% of production costs and limiting sectoral growth, particularly for smallholder farmers. This review critically analyzes Kenya's fish feed sector through an integrated PESTEL‐SWOT framework, drawing on a scoping review of academic literature, policy reports, and sector development studies. The paper highlights key macro‐level drivers, including fragmented policy implementation, dependency on imported ingredients, and climate‐related risks, and connects these with internal industry dynamics such as innovation gaps and regional disparities in aquafeed accessibility. It presents a conceptual model illustrating how external and internal factors interact to shape aquafeed sector outcomes, positioning Kenya's experience within a broader Sub‐Saharan Africa aquaculture context. The review identifies missed opportunities in scaling insect‐ and microalgae‐based feed innovations, constrained by regulatory, technical, and market barriers. The discussion offers actionable recommendations for researchers, policymakers, donors, investors, and industry stakeholders, emphasizing the importance of integrated policy reforms, investment in local aquafeed technology development, and regional collaboration to strengthen feed supply resilience and address production bottlenecks.